EFEKTIVITAS LATIH KANDUNG KEMIH TERHADAP PERCEPATAN PERKEMIHAN PADA IBU PASCA SALIN DI RSUD KABUPATEN SORONG - Vera Iriani Abdullah; Jimmy Chandra (Nursing Arts, 2018)
SDgs targeting in 2030, the global maternal mortality rate can reach 70 per 100.000 live births. In indonesia, bleeding contributes the most maternal mortality and around 16-17% cases are caused by uterine atony due to urinary retention. Which prevents the uterus from contracting properly because the uterus is pushed up and sideways. Vaginal delivery and worries due to pain result in the inability to excrete urine which can cause complication of uremia, infection, sepsis, an even spontaneous rupture of urinary vesicles. Training bladder 2-hours postpartum is one of interventions that can be done so that mother can return to normal urinary pattern and prevent bleeding that results in death. The purpose of this study was measure the effectiveness of bladder training on the acceleration of post partum maternal urination at the Sorong district hospital in 2018. The result of this study we expected to be a reference for complementary therapies to overcome cases of urin retention in post partum mothers. This research method uses a quasi experimental method with a cross sectional approach. The result of hypothesis using kruskal-walls showed a p value >0,05, that’s mean there was no effectiveness of bladder training on the acceleration of post partum maternal urination at the Sorong district hospital.